Applying the extended attitude formation theory to central bank digital currencies - Frédéric Tronnier; David Harborth; Patrick Biker (Electronic Markets, 2023)
This work analyzes the attitude formation process of individuals for central bank digital currencies (CBDCs), specifically for the digital euro. CBDCs are heavily researched, with pilot projects being conducted worldwide. Following the emergence of cryptocurrencies and a decrease in cash usage for retail transactions, CBDCs are viewed as the possible payment solution of the future. Using a qualitative approach, we conduct expert and non-expert interviews to apply and extend existing research on attitude formation to study how individuals form attitudes towards a CBDC in Germany. We find that individuals form their attitudes towards a digital euro through the perceived benefits, limitations, and concerns regarding related payment solutions, moderated through the perceived equivalence of these related technologies and the CBDC. The results contribute to the literature on CBDC and can be used by practitioners to develop a digital euro that offers a competitive advantage for retail transactions over established payment solutions.
Keywords: O33; G41; 620; Central bank digital currency; Attitudes; CBDC; Digital euro; Attitude formation theory; Technology adoption